Faktor Yang Mempengaruhi Rumah Tangga Untuk Mengakses Lembaga Keuangan Formal: Studi Kasus SUSENAS 2015 - tri achya ngasuko (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
World Bank in 2014 reported only 36% of Indonesians have access to formal financial institutions. This number shows the level of financial inclusion in Indonesia. There is still some task to do since Indonesian government has the goals 70% level of financial inclusion in 2019. The BPS survey, Susenas 2015, has new information on household saving profiles. This information is not available in the previous Susenas survey. This study is the first to examine influencing factors for heads of households accessing formal financial services, particularly savings, based on Susenas 2015. The results of this study provide household profiles and influencing factors for heads of households to access formal financial institutions, especially savings. Using the logit model, the probability for households to have savings in formal institutions is positively influenced by demographic characteristics such as age, number of family members, dependents of family head parents, male family heads, formal employment of heads of households, and credit ownership head of family. While the number of dependents of children, the field of work of the head of the family in the agricultural sector, and location of head of household in rural area negatively affect the ownership of savings accounts. The findings of this research are crucial in providing policy recommendations to improve the level of inclusive finance in Indonesia. Keywords: financial inclusion, household saving, Susenas 2015